RANCANGAN INOVASI LAYANAN MOBILITAS DI DALAM KAMPUS DENGAN METODE DESIGN THINKING - Muhamad Roihan AlAzhari; Didit Widiatmoko Soewardikoen; Hanif Azhar; Mahendra Nurhadiansyah; Hanindito Prabandaru (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2025)
Campus transportation at Telkom University plays a crucial role in supporting university community mobility and facilitating academic interactions and social activities. However, there are challenges affecting user satisfaction. This research employs a design-oriented approach using Design Thinking methodology to develop innovative solutions to enhance campus transportation efficiency. The analysis revealed that users desire a well-integrated transportation system, real-time information on schedules and vehicle locations, and the use of digital payment technologies. In response to these findings, a prototype of the TelU Mobility Assistant application was developed and tested using the System Usability Scale (SUS), which indicated favorable acceptance rates among users. The benefits of this study include improving efficiency and user satisfaction in campus mobility while reinforcing Telkom University's reputation as an institution focused on innovative solutions and optimal user experiences.